Does having more power make people more materialistic? The role of personal sense of power for gift preferences - Liang, Shichang; Han, Xiaoyan; Yuan, Xueying; Liang, Meiting; Zhang, Yiwei; Liu, Zhen; Xie, Pin (Frontiers in Psychology, 2023)
Introduction Gift-giving is a prevalent practice in daily life, with experiential gifts being identified in studies as having hedonic and interpersonal advantages, often yielding greater recipient satisfaction compared to material gifts. However, the reception of experiential gifts might not always align with expectations, as material gifts are valued for their enduring qualities. Thus, comprehending the contexts favoring material or experiential gift preferences becomes crucial. Methods Existing research primarily delves into external influences like income and social proximity, while intrinsic factors such as personal sense of power in interpersonal interactions have received limited attention. Guided by the Agentic-communal Model of Power, we conducted three studies to investigate how personal sense of power impact gift preferences. Results Our findings demonstrated that gift preferences are contingent upon personal sense of power. Specifically, those possessing a high personal sense of power exhibited a preference for material gifts over experiential ones, whereas individuals with a low personal sense of power favored experiential gifts over material ones. Further analysis revealed that the relationship between personal sense of power and gift preference is mediated by information processing fluency. Discussion This study contributes to the field of gift preferences and sheds light on the role of personal sense of power. By incorporating the Agentic-communal Model of Power, we offer novel insights into the dynamics between personal sense of power and gift preferences. These findings hold valuable implications for managerial strategies concerning gift selection and interpersonal interactions.